Plant Biostimulants to Enhance Abiotic Stress Resilience in Crops - Di Sario, Luciana (2025)
The escalating impact of abiotic stress on crop productivity requires innovativestrategies to ensure sustainable agriculture. This review examines the promising role of biostimulants in mitigating the adverse effects of abiotic stress on crops. Biostimulants, rangingfrom simple organic compounds to complex living microorganisms, have demonstratedsignificant potential in enhancing plant resilience, stress tolerance, and overall performance.The mechanisms underlying biostimulant action—such as enhancing antioxidant defenses,regulating hormonal pathways, and inducing metabolic adjustments—are reviewed. Furthermore,we incorporate the latest research findings, methodologies, and advancements inbiostimulant applications for addressing abiotic stressors, including drought, salinity, hightemperatures, and nutrient deficiencies. This review also highlights current challenges andfuture opportunities for optimizing biostimulant use in sustainable crop production. Thisrevision aims to guide researchers and agronomists in applying biostimulants to improvecrop resilience in the context of climate change.